2016
DOI: 10.1108/bij-09-2013-0093
|View full text |Cite
|
Sign up to set email alerts
|

Efficiency ranking method using DEA and TOPSIS (ERM-DT): case of an Indian bank

Abstract: Purpose – The purpose of this paper is to present a tie-breaking procedure for computing performance efficiencies to improve benchmarking and performance evaluation process in a business situation. Design/methodology/approach – The authors propose a unified approach based on data envelopment analysis (DEA) and technique for order of preference by similarity to ideal solution (TOPSIS), to overcome the difficulty of unique ranking in the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(21 citation statements)
references
References 42 publications
0
21
0
Order By: Relevance
“…TOPSIS concept is based on a simple idea, which is, that the optimal ideal solution should have the maximum benefits from the positive-ideal solution and should have the minimum benefits from the negative-ideal solution. Here, the positive-ideal solution is identified from the best alternative whereas the negative-ideal solution is from the most unsuitable alternative (Chitnis and Vaidya, 2016;Sarkar, 2013;Srikrishna et al, 2014). The overall steps and methodology of TOPSIS SIMOS is given below (refer to Sreedharan et al, 2018 for detailed steps on this MCDM technique).…”
Section: Methodsmentioning
confidence: 99%
“…TOPSIS concept is based on a simple idea, which is, that the optimal ideal solution should have the maximum benefits from the positive-ideal solution and should have the minimum benefits from the negative-ideal solution. Here, the positive-ideal solution is identified from the best alternative whereas the negative-ideal solution is from the most unsuitable alternative (Chitnis and Vaidya, 2016;Sarkar, 2013;Srikrishna et al, 2014). The overall steps and methodology of TOPSIS SIMOS is given below (refer to Sreedharan et al, 2018 for detailed steps on this MCDM technique).…”
Section: Methodsmentioning
confidence: 99%
“…Asmita Chitnis, et al (2016) [8] proposed a unified approach based on DEA and TOPSIS to overcome the difficulty of unique ranking in the prevalent benchmarking and performance evaluation processes. The authors presented a case of an Indian bank to illustrate an application of the proposed approach.…”
Section: Literature Surveymentioning
confidence: 99%
“…Mohammad, et al (2016) [9] identified the criteria and their coefficients used for financial performance evaluation of private banks using the fuzzy AHP method. After that, the authors evaluated financial performance of Iran private banks and ranked them using the information on the financial statements through TOPSIS method Mehdi Fallah Jelodar (2016) [10] prioritized the factors affecting performance efficiency in the areas of management, personnel, finance, and customers using the methods of DEA and hierarchical analysis.…”
Section: Literature Surveymentioning
confidence: 99%
“…Then, TOPSIS method was applied to sort out these alternatives and find the best alternative (Chitnis & Vaidya, 2016). The results show that while Hong Kong, USA and India rank the first three in terms of tourism sector efficiency, Mexico (19) and Russia (18) are in the last rank.…”
Section: Efficiency (1)mentioning
confidence: 99%